Distillation synthesis toolbox for pre-flowsheet design - Wilson, Cameron Joseph (My University, 2007)
Preliminary evaluations during flowsheet synthesis require simple effective tools for comparison and elimination of process alternatives. This work investigates three areas of interest in distillation. Column profile map theory has simplified complex column investigations. The predictions of the difference point equation at finite reflux were experimentally verified for the acetone, methanol and ethanol system in a continuous column apparatus. Residue curve analysis is usually limited to systems with four components for distillation system analysis. An alternative representation, based on combinatorial topology and temperature sequencing, is introduced for use in high level synthesis decisions for higher component order systems. Attainable region (AR) theory is applied to an ideal binary distillation system for a geometrically based method of cost analysis. A constrained attainable region is constructed from a series of equilibrium step compositions with varying reflux and corresponding cost associations. The AR is shown to be useful for costing and optimization.
Student Number : 9903549T - MSc dissertation - School of Process and Materials Engineering - Faculty of Engineering and the Built Environment
Keywords: Distillation; Column Profile Maps; Residue Curves; Experimental; Higher Order; Chain Maps; multicomponent; costing Capacity